Exploring Homogeneous Ni and Ru Complexes for Thermal and Photocatalytic Acceptorless Alcohol Dehydrogenation and Photocatalytic Carbon Dioxide Reduction - Mohamad, Eman M KH (Université d'Ottawa | University of Ottawa, 2026)
This thesis explores the design and application of homogeneous nickel and ruthenium complexes for acceptorless alcohol dehydrogenation under thermal and photocatalytic conditions, as well as for the photocatalytic reduction of carbon dioxide. These transformations are of significant interest for sustainable energy conversion, as they enable hydrogen production and carbon utilization without the need for sacrificial reagents. Emphasis is placed on understanding how ligand architecture, metal-ligand cooperation, and light influence catalytic activity and reaction mechanisms. The first part of this work investigates hydrogen generation through photocatalytic acceptorless alcohol dehydrogenation using a homogeneous nickel complex. Under visible-light irradiation at room temperature, the nickel system selectively produces hydrogen from alcohol substrates. This work demonstrates that dimethylethanolamine (DMEA) functions as an effective electron donor, significantly improving photocatalytic hydrogen generation in the nickel system. Mechanistic studies supported by density functional theory calculations were performed. These results show that ligand flexibility and metal-ligand cooperation play critical roles in facilitating key steps of the catalytic cycle. The second part of the thesis examines acceptorless alcohol dehydrogenation enabled by homogeneous RuPN3P pincer complexes under both thermal and visible-light-driven conditions. These studies demonstrate that RuPN3P systems efficiently promote alcohol dehydrogenation and that light irradiation can further influence catalytic behavior. Detailed mechanistic analysis highlights the importance of metal–ligand cooperation, particularly the involvement of proton- responsive ligand sites in hydrogen formation. The final part of this thesis focuses on the photocatalytic reduction of carbon dioxide to formic acid using ruthenium catalysts supported by PN ligands. The results show that appropriate ligand design facilitates CO2 activation and enables selective formic acid production under visible-light. Collectively, the findings presented in this thesis advance the development of homogeneous catalytic systems for sustainable hydrogen production and carbon dioxide conversion. These results also provide design principles relevant to energy-related catalytic transformation.
Keywords: Homogeneous catalysis; Acceptorless alcohol dehydrogenation; Photocatalysis; Hydrogen production; Nickel complexes; Ruthenium complexes; Pincer ligands; Metal–ligand cooperation; Visible-light irradiation; CO₂ reduction; Formic acid production; Sustainable energy conversion